2017
DOI: 10.1074/jbc.m116.773861
|View full text |Cite
|
Sign up to set email alerts
|

The natural phosphoinositide derivative glycerophosphoinositol inhibits the lipopolysaccharide-induced inflammatory and thrombotic responses

Abstract: Inflammatory responses are elicited through lipid products of phospholipase A activity that acts on the membrane phospholipids, including the phosphoinositides, to form the proinflammatory arachidonic acid and, in parallel, the glycerophosphoinositols. Here, we investigate the role of the glycerophosphoinositol in the inflammatory response. We show that it is part of a negative feedback loop that limits proinflammatory and prothrombotic responses in human monocytes stimulated with lipopolysaccharide. This inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…It has been shown that endogenous metabolites, such as succinate and itaconate, may play separate roles to regulate inflammatory responses [11,12]. In addition, increases in the intracellular glycerophosphoinositol level of macrophages can be observed in lipopolysaccharide-induced inflammation, probably reflecting a modulatory effect on inflammatory responses [13]. Systemic metabolic adaptations during neonatal sepsis have been demonstrated [14] but the effect on cerebral energy metabolism is less known, though it may be of importance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that endogenous metabolites, such as succinate and itaconate, may play separate roles to regulate inflammatory responses [11,12]. In addition, increases in the intracellular glycerophosphoinositol level of macrophages can be observed in lipopolysaccharide-induced inflammation, probably reflecting a modulatory effect on inflammatory responses [13]. Systemic metabolic adaptations during neonatal sepsis have been demonstrated [14] but the effect on cerebral energy metabolism is less known, though it may be of importance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is known that the levels of GroPIns upon transformation or differentiation do not follow the same pattern in all cells, but depend on the active signaling pathways including specific oncogenes or cPLA 2 α activities ( 6 , 7 , 11 , 19 , 29 ). Likewise, it has been shown that GroPIns participates in the resolution of the inflammatory response ( 17 ) and that its release from activated macrophages could induce T cell activation via a paracrine mechanism ( 27 , 34 ). Now it will be possible to mimic these different conditions in vitro and investigate the GroPIns mechanism of action by revealing its dynamic behavior and target/s and shedding light on its putative paracrine role.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, treatment of A375MM (human melanoma) and MDA-MB-231 (human mammary carcinoma) cells with GroPIns inhibited their migration in in vitro models of extracellular matrix invasion ( 16 ). Furthermore, GroPIns acted as an anti-inflammatory factor by blocking the signaling cascade triggered by LPS in primary human monocytes, including NF-κB translocation to the nucleus ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Receptors activating the cPLA 2 α/glycerophosphoinositol pathway include adrenergic, purinergic and tyrosine kinase receptors such as epidermal growth factor (EGF) or insulin [3–5]. Also lysophosphatidic-acid receptor in fibroblasts [6], Fc receptor in macrophages [7], lipopolysaccharide-TLR4 in human monocytes [8] lead to glycerophosphoinositol production by activating cPLA 2 α. The glycerophosphoinositol formation is particularly abundant in hematopoietic cells where these compounds are involved in multiple signalling pathways in the context of inflammation and immune reactions [9], generally exerting inhibitory effects [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Also lysophosphatidic-acid receptor in fibroblasts [6], Fc receptor in macrophages [7], lipopolysaccharide-TLR4 in human monocytes [8] lead to glycerophosphoinositol production by activating cPLA 2 α. The glycerophosphoinositol formation is particularly abundant in hematopoietic cells where these compounds are involved in multiple signalling pathways in the context of inflammation and immune reactions [9], generally exerting inhibitory effects [7, 8]. In addition, a major effect of glycerophosphoinositol 4-phosphate (GroPIns4 P ; the phosphorylated form of glycerophosphoinositol, GroPIns) is the regulation of the actin cytoskeleton dynamics in fibroblasts and immune cells [1012].…”
Section: Introductionmentioning
confidence: 99%